Hubungan Paritas, Hipertensi dan Jarak Kelahiran dengan Kejadian BBLR di RSUD Kayuagung Tahun 2021 - Deli Luspalestari; Siti Aisyah; Erma Puspita Sari (Universitas Batanghari Jambi, 2023)
Low Birth Weight (LBW) is a baby born with a weight less than 2500 grams which has a contribution to infant mortality, especially during the perinatal period. LBW is caused by a short gestational age (prematurity) and IUGR (Intra Uterine Growth Restriction) which in Indonesian is called Inhibited Fetal Growth (PJT) or both. Both of these causes are influenced by risk factors. Factors associated with the incidence of LBW are maternal age, gestational age, parity, gestational age, malnutrition during pregnancy, hypertension, smoking, multiple pregnancy, hydramnios, tiring work and birth spacing. This study aims to determine the relationship between parity, hypertension and birth spacing with the incidence of low birth weight in the Kayuagung Hospital in 2021. The design of this research is quantitative using an analytical survey method with a cross sectional approach. The population in this study were all newborns at the Kayuagung Hospital in 2021 as many as 1004 babies. The sample used was some newborns in the Perinatal Room of RSUD Kayu Agung, amounting to 91 respondents. The statistical results of the chi-square test obtained p value = 0.003 < 0.05, so it can be concluded that there is a relationship between parity and the incidence of LBW, the statistical results of the chi-square test obtained p value = 0.275 <0.05, so it can be concluded there is no relationship between hypertension and the incidence of LBW and the statistical results of the chi-square test obtained p value = 0.010 <0.05, so it can be concluded that there is a relationship between birth spacing and the incidence of LBW. It can be concluded that there is a relationship between parity and birth spacing with the incidence of LBW at the Kayuagung Hospital in 2021 and there is no relationship between hypertension and the incidence of LBW at the Kayuagung Hospital in 2021.